A randomized controlled trial to study the effect of gross myofascial release on mechanical neck pain referred to upper limb - Gauns, Sweta V.; Gurudut, Peeyoosha V. (International Journal of Health Sciences, 2018)
Objective: Mechanical neck pain (NP) with referred pain to upper limb is a common problem and often leads to functional impairment of common activities of daily living. The present study is undertaken to study and compare the effect of gross myofascial release (MFR) of upper limb and neck alone with conventional physiotherapy against only conventional treatment in subjects with mechanical NP referred to upper limb in terms of cervical endurance, pain, range of motion, and function. Methods: Design: This was a experimental study; a total of 40 subjects clinically diagnosed with mechanical NP along with referred pain between the age group of 20 and 50 years. Intervention: Control group was given conventional treatment of hot moist pack, TENS, and stretching and strengthening exercise, and experimental group was given gross MFR of the neck and upper limb in addition to conventional therapy. Treatment was given for 6 consecutive days. Outcome measures used were pressure biofeedback to measure cervical endurance, goniometer for cervical ROM, Northwick Park NP questionnaire, and disabilities of arm, shoulder, and hand questionnaire. Results: Statistically significant change was present for pain, cervical flexure endurance, ROM, and functional abilities with P < 0.05 for both the groups except for neck flexor endurance in control group. Conclusion: Gross MFR of upper limb and neck is an effective technique for subjects with mechanical NP and has a faster rate of improvement.